Estrategias lúdicas para mejorar el proceso de enseñanza aprendizaje de las Ciencias Naturales. - Sailema León, Elsa Jeaneth (2018)
Knowing the great importance of the game in the development of all students' other skills, this study is intended to respond to a severe issue that has existed in the school population: the lack of fun of the child that allows him/her to interact more often with others which causes the absence of companionship and collaborative work. In these circumstances it was considered urgent to contribute with a study-problem that has become common in the institutions of the educational system where the passive role of the student associated with the way of addressing the issues by teachers causes a state of pedagogical lethargy, generating unpleasant feelings, such as fatigue, discouragement, indifference, and loneliness. The objective of this research was to determine the importance of recreational activities as a methodological strategy in the teaching-learning process of the Natural Sciences area in the Seventh Grade of Basic General Education at the Educational Unit "Manuel Gonzalo Albán Rumazo" in the school year 2017-2018. The results of the investigation reveal serious limitations about the classroom management of teachers for the concretion of the skills in grade and level; therefore, the importance of the research is dimensioned in the recommendation of operational strategies of playful work, so teachers through a didactic planning reaches a significant learning in the area of Natural Sciences into their students.